Eco-friendly sustainable fluorescent carbon dots for the adsorption of heavy metal ions in aqueous environment - Pudza, Musa Yahaya; Zainal Abidin, Zurina; Abdul Rashid, Suraya; Md. Yasin, Faizah; Muhammad Noor, Ahmad Shukri; Issa, Mohammed Abdullah (MDPI, 2020)
The materials and substances required for sustainable water treatment by adsorption technique, are still being researched widely by distinguished classes of researchers. Thus, the need to synthesize substances that can effectively clean up pollutants from the environment cannot be overemphasized. So far, materials in bulk forms that are rich in carbon, such as biochar and varieties of activated carbon have been used for various adsorptive purposes. The use of bulk materials for such purposes are not efficient due to minimal surface areas available for adsorption. This study explores the adsorption task at nano dimension using carbon dots (CDs) from tapioca. The properties of carbon structure and its influence on the adsorptive efficacy of carbon nanoparticles were investigated by energy-dispersive spectroscopy (EDS), X-ray photoelectron spectroscopy (XPS), Fourier transform infrared spectroscopy (FTIR), high resolution transmission electron microscopy (HrTEM), and atomic force microscopy (AFM). The results implied carbon present in CDs are good adsorbents for effective adsorption of heavy metal ions (lead) with removal efficiency of 80.6% in aqueous environment. The adsorption process as explored by both Langmuir and Freundlich isotherms have proven favorability of the adsorption process. Langmuir form two and three have correlation coefficients R2 at 0.9922 and 0.9912, respectively. The Freundlich isotherm confirms CDs as having defined surface heterogeneity and the exponential distribution of active sites. The adsorption of lead unto CDs obeyed the second order kinetic model with coefficient of determination, R2 of 0.9668 and 0.9996 at an initial lead concentration of 20 mg/L and 100 mg/L, respectively. The findings validated the efficiency of CDs derived from tapioca as an excellent material for further utilization in the environmental fields of wastewater pollution detection and clean up, bio-imaging, and chemical sensing applications.